Parasitic Diseases that Cause Seizures: Parasitic Diseases that Cause Seizures. Issue 2 (January 2014) - Nash, Theodore E.
The propensity of parasites to invade the brain, cause disease, and give rise to seizures and epilepsy varies greatly. This reflects the wide diversity of parasites that differ in fundamental ways. This manuscript reviews parasites that invade the brain or its vasculature and give rise to seizures.